Implementasi Chatbot Untuk Membantu Wisatawan Dalam Mencari Wisata Yang Berada Di Kabupaten Semarang Dengan Menggunakan Metode Natural Language Processing (NLP) - Putri, Risqa Verolina Sonia Lestari; Utomo, Mardi Siswo (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Tourism is an important sector in the economic growth of a region. In the current digital era, chatbot technology based on Natural Language Processing (NLP) has become an innovative solution to facilitate interaction between humans and machines. This research aims to develop a chatbot that can help tourists find tourist destinations located in Semarang Regency. This Chatbot development method involves analyzing user needs, collecting tourist destination data, and implementing Natural Language Processing (NLP) algorithms to understand tourist questions and requests. This chatbot is designed to provide accurate and relevant information based on tourist questions, thereby improving the user experience in searching for tourist destinations in Semarang Regency.